Mérni a mérhetetlent? A megyei jogú városok vizsgálata többdimenziós skálázással - Lengyel, Imre (Tér és Társadalom, 1999)
In my study I adopt the methodology of multidimensional scaling for analysing the disparity between Hungarian towns. I analyse all the 22 towns of county rank, have more than 50 thousand inhabitants (except of Budapest). The difference between development levels of towns is analysed by 50 indicators based on data of 1996. We lay emphasis on development of towns to one another with 30 indicators composed of data resulted censuses of 1980 and 1990. There are three types of indicators: data of population and employment, data of infrastructure owned by inhabitants, indicators related to economic basis. We use ALSCAL routine of SPSS 8.0 program package, and it was nin in the Department of Regional and Applied Economics in JATE (Szeged). One of the most important results is the significant differentiation of town types. Towns of developed Western and Central Transdanubia are situated closed to each other in the figure of multidimensional scaling, so they have many similar characteristics. Towns of regions lagging behind, regions are in industrial decline and towns show agricultural characteristics are diffused and set far away from the developed towns. With comparison the two censuses it might be seen that there was just a small change in the difference between towns, nevertheless after 1990 a different development started in the urban network. In the northern part of Transdanubia new jobs have been established, foreign investments have been appeared, small and medium sized enterprises have became more active, etc: In this region a dynamic growing has started, while in other parts of the country the measure of changing is more disadvanced.